A review of the challenges and prospects for Islamic tourism policies in Malaysia - Hassan, Mohamad Ghozali; Razalli, Mohd Rizal; Musa, Umar Farouk (Academic Research Publishing Group, 2018)
Statistics attested that Malaysia is ranked the 1st as the hub for Islamic tourism among the organization of Islamic cooperation members’ state. Despite these achievements, literature indicated some conspicuous challenges affecting Islamic tourism policies in the country. This study uses secondary data to examine the barriers militating against Islamic tourism and put forward some prospects; policy recommendations respectively. Findings from our review reveals that the country had executed 10 different master plan, but poor policy guidelines, paucity of researches and market difficulty were some of the challenges affecting the sector, while other predicaments to Islamic tourism in the areas of Shariah compliant hotels, promotion of halal products, were underutilized. Two propositions were established to accelerate in identification of the challenges and prospects for Islamic tourism in the study area. We have suggested for policy guidelines, the revitalization of the image of Islamic tourism, provision of modern infrastructure, and utilization of the natural, historic and other Islamic center to attract visitors from all parts of the world. Islamic tourism required diversity in the market, especially through specific needs, beliefs, tastes, expectation and global competitiveness